Clinical and neuroimaging insights into childhood arterial ischemic stroke of different ages - Liu, Guanhao; Ding, Qiang; Wang, Bohao; Hu, Qianhong; Sun, Mengmeng; Liang, Yafeng; Zhao, Qianlei (Frontiers in Neurology, 2025)
BackgroundChildhood stroke is a neurological emergency and an important cause of acquired brain injury and mortality in children. This retrospective study aimed to investigate the clinical presentation and neuroimaging features of arterial ischemic stroke (AIS) in children.MethodsWe retrospectively reviewed the records of pediatric AIS including neonates and children under 18 years of age from January 2008 to December 2023. Then we analyzed the gender and age distribution of AIS, as well as the clinical and neuroimaging characteristics and risk factors of AIS in different age groups. The study was approved by the Ethics Committee of the host institution.ResultsMale patients predominated in both the neonatal AIS (NAIS) group and the pediatric AIS (PAIS) group. The majority of AIS children (73, 60.33%) were diagnosed after 24 h of symptom onset. Seizures (82.35%) and limb weakness (77.88%) were the most common initial neurologic symptoms of NAIS and PAIS, respectively. Anterior circulation AIS alone was much more common than posterior circulation AIS alone in childhood AIS (79.34% vs. 9.92%). However, the NAIS group had a higher rate of infarctions that solely involved the cortex (52.94% vs. 20.19%). Perinatal hypoxia or asphyxia (23.5%) and minor head injury (28.85%) were the most common possible risk factors in NAIS and PAIS, respectively.ConclusionAIS in children is male-predominant, and there is significant diagnostic delay in both NAIS and PAIS. NAIS and PAIS differ in clinical and neuroimaging manifestations, and risk factors. Notably, we also noted that the actual prevalence of AIS in children, and the diagnosis of certain risk factors, may be underestimated. Education and training will be necessary in both layperson and healthcare settings. Furthermore, prospective studies are required to explore this hypothesis.